Molecular characterization of ornamental fish species (poeciliidae) using mitochondrial dna12s rRNA anD 16S rRNA genes - Ghazali, Siti Norsywazni (Universiti Sains Malaysia, 2015)
Mitochondrial DNA (mtDNA) ribosomal genes have been used as molecular markers for fish species identification in many studies. In this study, two mtDNA ribosomal genes namely 12S rRNA and 16S rRNA have been utilized to characterize ornamental fish species from Peocilidae family. Five ornamental fish species namely Poecilia sphenops, Poecilia reticulata, Limia vitatta, Xiphophorus hellerii and Xiphophorus maculatus were selected. PCR amplification was performed and DNA sequencing was carried out in order to study the genetic relationship of fish species. Phylogenetic tree results showed that two different group of fish species were found with one groups consists of Limia vitatta, Xiphophorus hellerii and Xiphophorus maculatus. The second group consists of Poecilia sphenops and Poecilia reticulata. Interestingly, both mtDNA ribosomal genes showed similar result for neighbor joining tree.